PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA BELAJAR IPA SISWA KELAS IV SDN 015 GERINGGING JAYA - Supono Supono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Efforts to improve science learning outcomes through the application of cooperative learning model type STAD grade 4 students SDN 015 Geringging Jaya Kuantan Singingi Regency. Lesson Year 2014/2015 is based on many students who can not understand the learning materials. The purpose of this study is to determine the improvement of learning outcomes of learners through the application of STAD type cooperative learning modes in natural science classes grade IV SDN 015 Geringging Jaya in the even semester. This study is a class action carried out by teachers who teach in the classroom. The data collected is teacher's teacher's and student activity data which is divided into two cycles. Each cycle has four stages: planning, action, observation and reflection. The subjects of this study were the fourth graders of SDN 015 Gringginga Jaya which consisted of 16 students consisting of 9 male students and 6 female students. The results showed that the application of STAD type learning module can improve student learning outcomes of fourth grade students of SDN 015 Geringging Jaya with total number of students who completed in pre cycle as many as 5 students, cycle I with 6 students and cycle II 16 students.